EXPERIMENTAL VALIDATION OF OPTIMUM RESISTANCE MOMENT OF CONCRETE SLABS REINFORCED WITH CARBON FIBRE-REINFORCED PLASTIC (Nigerian Journal of Technology, 2017)
Fibre-Reinforced Plastics (FRPs) have been suggested as suitable reinforcement for concrete structures among other solutions to combat corrosion problems in steel reinforced concrete. This paper presents the experimental validation of optimum resistance moment of concrete slabs reinforced with Carbon-Fibre Reinforced Plastic (CFRP). Eight specimens of two-way spanning slabs reinforced with CFRP bars were used in the experiment. They were designed to achieve two classical failure modes: rupture of the reinforcements (tension failure) and crushing of the concrete while the reinforcement remains elastic (compression failure). This was accomplished by using reinforcement ratios less, and more than the balanced reinforcement ratio,, for the slabs, respectively. All the slabs failed as predicted. The results obtained show that the design formulations for predicting the minimum flexural resistance of an CFRP-reinforced concrete member provided by CSAS806-02(R07) have been underestimated. The design formulations were found to underestimate the resistance moment capacity of CFRP-reinforced concrete slabs by about 33%. http://dx.doi.org/10.4314/njt.v36i2.9